Permodelan reaktor sharon dengan umpan urea-amonia - Tjandra Setiadi; Indrie Ratnasari; Trimaharika Widarena (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2007)
SHARON (Single reactor High activity Ammonia Removal Over Nitrite)-Anammox (Anaerobic Ammonium Oxidation) has never been used for treating wastewater with high urea content. Three prior researches have been done to examine the performance of SHARON process with urea-ammonia feed but the results are still unable to explain its performance. To explain these results, a model of SHARON process is needed to be built. Based on material balances of SHARON process in a stirred tank reactor, a model was built. The model is nonlinear differential equation system and was solved using Least Square Method with the help of MATLAB. The simulation result shows that nitrate was always occurred in the effluent of the SHARON process. Based on this research, equimolar nitrite to ammonia ratio can be obtained only if the feed is equimolar in urea and bicarbonate composition. Optimized kinetic parameter obtained are μmaxamm = 1,16E-05 s-1, μmaxnit = 3,998E-05 s-1, KNH3amm = 3,346E-02 mol mL-3, Kl,HNO2amm = 1,45E-02 mol mL-3, Kl,HNO2amm = 6,14E-03 mol mL-3. This result show that there are inhibition in oxidizing ammonium in the reactor and inhibition on growth of the nitrite oxidizer. Keywords : modelling, SHARON, urea-ammonia, kinetic parameter Abstrak Proses SHARON (Single reactor High activity Ammonia Removal Over Nitrite)-Anammox (Anaerobic Ammonium Oxidation) belum pernah digunakan untuk mengolah air limbah dengan konsentrasi urea tinggi. Data-data yang diperoleh dari percobaan pendahuluan belum dapat menjelaskan unjuk kerja reaktor SHARON dengan umpan berupa urea-amonia. Oleh karena itu, perlu disusun pemodelan matematika untuk menentukkan parameter kinetika pertumbuhan mikroba dan parameter stoikiometrik reaksi yang terjadi pada reaktor SHARON. Penyusunan model dilakukan berdasarkan neraca massa reaktor tangka reaktor kontinyu berpengaduk. Model yang dihasilkan berupa system model menunjukkan bahwa konsentrasi nitrat sama dengan nol pada keluaran reaktor SHARON dengan umpan urea-amonia tidak dapat dicapai. Untuk mendapatkan nisbah nitrit terhadap nitrat yang ekuimolar, diperlukan umpan dengan komposisi urea dan bikarbonat yang ekuimolar. Parameter kinetic yang diperoleh dari hasil optimasi model adalah μmaxamm = 1,16E-05 s-1, μmaxnit = 3,998E-05 s-1, KNH3amm = 3,346E-02 mol mL-3, Kl,HNO2amm = 1,45E-02 mol mL-3, Kl,HNO2amm = 6,14E-03 mol mL-3. Kata Kunci : pemodelan, SHARON, urea-amonia, parameter kinetik